Pembuatan Alat Uji untuk Mengikat Partikel Logam yang Terkandung dalam Pelumas Akibat Gesekan Mesin - Sukamta, Sukamta; Sudarja, Sudarja; Nurdarojat, Nurdarojat; Prasetyo, Agung (Semesta Teknika, 2014)
One of the factors that can affect to the quality of lubricantion is metal particle content due to friction of engine parts. Metal particle in lubricanting oil could damage the engine parts, so it is neccessary to reduce the metal particle content which mingled in lubricant oil. The experiment was conducted in laboratory scale using power magnetic type ring neodymium possessing diameter of 19 mm and thickness of 2 mm. The experiment was conducted by flowing the lubricanting oil containing metal particle continually and put the magnets in engine so that the metal particle will be taken up by the magnets. The experiment used three variations of time (5, 10 and 15 minutes) and three variations of valve to controlling the flow rate using. The highest absortion of metal particle was reached on opening valve 30 for 15 minutes. When volume the flow rate was 200 ml/s and the time was 15 minutes the result of absortion was 7.48 % (magnet A), meanwhile for volume the flow rate 180 ml/s and the time was 15 minutes resulted in particle absortion of about 7.37 % (magnet B). When Magnet A and B used together and at the same flow rate and time, i.e. 180 ml/s time 15 minutes, resulted the particle absortion about 17.98 %.